2010
DOI: 10.1016/j.actamat.2010.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Spacing characterization in Al–Cu alloys directionally solidified under transient growth conditions

Abstract: We study spacing selection in directional solidification of Al-Cu alloys under transient growth conditions. New experimental results are presented which reveal that dendritic spacing versus solidification rate evolves in an almost step-wise fashion, consistent with previous theoretical predictions of Langer and co-workers. Phase field simulations of directional solidification with dynamical growth conditions approximating those in the experiments confirm this behavior. Changes in dendrite arm spacing is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 19 publications
(49 reference statements)
1
30
0
Order By: Relevance
“…A logical test of the phase-field theory would be to calculate the so-called "pinch-off time" for the filaments here, that is, the time it takes for a Rayleigh instability in the filament to amplify and cause the filament diameter to reduce to zero locally [41] . This class of topological singularity has been the subject of recent theoretical interest [42] , and a framework has been developed allowing pinch-off to be predicted, verified through measurements of the µm-scale evolution of dilute binary alloys using x-ray tomography [43] .…”
Section: Cellular Breakdown Dynamicsmentioning
confidence: 99%
“…A logical test of the phase-field theory would be to calculate the so-called "pinch-off time" for the filaments here, that is, the time it takes for a Rayleigh instability in the filament to amplify and cause the filament diameter to reduce to zero locally [41] . This class of topological singularity has been the subject of recent theoretical interest [42] , and a framework has been developed allowing pinch-off to be predicted, verified through measurements of the µm-scale evolution of dilute binary alloys using x-ray tomography [43] .…”
Section: Cellular Breakdown Dynamicsmentioning
confidence: 99%
“…25 Phase-field simulations are thus capable of predicting stable dendritic spacing ranges in the steady state, 14,[26][27][28] as well as the dynamical selection of spacings by elimination during the transient stage of solidification. [28][29][30] Recent PF studies have also shown that, in polycrystalline columnar growth, the dynamical evolution of dendritic spacing at converging grain boundaries is closely linked to the unusual overgrowth mechanism of a favorably oriented grain. 16,31,32 While PF remains the method of choice for simulation of dilute alloy solidification, quantitative predictions of dendritic growth dynamics with PF require an accurate morphological description of each dendrite tip.…”
Section: Introductionmentioning
confidence: 99%
“…The linear growth rate and wavelength selection of cellular flame fronts are examined numerically, validating the recent analytical predictions of Brailovsky et al [24]. In the non-linear regime, we explore the growth of combustion morphologies that vary from cells to seaweed dendrites analogous to those observed in directional solidification [28,29]. This is seen to happen for low Le, a regime separating cellular/dendritic patterns from oscillatory modes prevalent at high Le.…”
Section: Introductionmentioning
confidence: 90%
“…A detailed analysis of spacing selection in the non-linear regime is beyond the scope of this work. Spacing selection in the non-linear regime has a long history in solidification studies [54,55] and while insight can be gained from analyses like the one above, it still represents a largely unsolved problem. front corresponds to isotherm θ(x, y) = θ ig for model parameters MM(n = 1; Le = 0.05; θ ig = 0.75).…”
Section: Effect Of Lewis Number On the Morphologymentioning
confidence: 99%